Umbilical Cord Blood Gas Pairs with Near-Identical Results: Probability of Arterial or Venous Source - Monneret, Denis; Stavis, Robert L. (American Journal of Perinatology, 2023)
Objective In studies of concomitant arterial–venous umbilical cord blood gases (CAV-UBGs), approximately 10% of technically valid samples have very similar pH and/or pCO2 values and were probably drawn from the same type of blood vessel. Without a way to objectively determine the source in these cases, it has been argued that most of these same-source CAV-UBGs are venous because the vein is larger and more easily sampled than the artery. This study aimed to calculate the probability of an arterial (ProbAS) or venous source (ProbVS) of same-source CAV-UBGs in the clinically and medicolegally important pH range of 6.70 to 7.25 using a statistical predictive model based on the cord blood gas values.Study Design Starting with a dataset of 56,703 CAV-UBGs, the ProbAS, ProbVS, and respective 95% confidence intervals (CIs) were calculated for the 241 sample pairs with near-identical pH, pCO2, and pO2 values and a pH of 6.70 to 7.25. Using a previously validated generalized additive model, the source was categorized as: Probable Arterial or Highly Probable Arterial if the ProbAS and CIs were >0.5 or >0.8, respectively; Probable Venous or Highly Probable Venous if the ProbVS and CIs were >0.5 or >0.8, respectively; or Indeterminant if the CIs encompassed ProbAS/VS = 0.5.Results A total of 39% of the same-source CAV-UBGs were Probable Arterial, 56% were Probable Venous, and 5% were Indeterminant. However, considering samples with a pH ≤7.19, 80% were Probable Arterial and 16% were Probable Venous. Considering the Highly Probable categories, the more acidemic specimens were 9 times more likely to be arterial than venous. Similarly, CAV-UBGs with pCO2 > 8.2 kPa (62 mm Hg) or pO2 ≤ 1.9 kPa (14 mm Hg) were more likely to be in the arterial rather than the venous categories.Conclusion Same-source CAV-UBGs in the more acidemic, hypercarbic, or hypoxemic ranges are more likely to be arterial than venous.Key Points
Keywords: umbilical cord; blood gas; arterial; venous; neonatal acidemia; probability; generalized additive model; GAM